Transformation of Santri Independence through My Day in Ma'had Program: A Cross-Site Approach in Two Probolinggo Islamic Boarding Schools - Moh Irfan Hadi; Abu hasan Agus RM (Al-Qalam Institute, 2023)
This research focuses on the analysis of strategies implemented by Nurul Yaqin Islamic Boarding School and Nurul Jadid Islamic Boarding School in Paiton, Probolinggo, in increasing student independence through the My Day in Ma'had program. The program is designed to develop students' emotional, behavioral, and value independence through different approaches in both boarding schools. The method used is a case study approach with data collection techniques in the form of field observations and in-depth interviews with kiai, ustadz, and students in both Islamic boarding schools. The results of the study show that the Nurul Yaqin Islamic Boarding School is more effective in accelerating the formation of student independence, especially in the aspects of behavioral and emotional independence, compared to the Nurul Jadid Islamic Boarding School which implements stricter supervision. This research has implications for the importance of balancing supervision and autonomy in the formation of student character in Islamic boarding schools. These findings can be used as a reference for the development of more effective character education programs in other Islamic boarding schools.